Meningkatkan Literasi Digital Guru Melalui Pemanfaatan Canva sebagai Media Pembelajaran di SMP N 2 Kota Ambon - Dewilna Helmi (Jurnal Informasi Pengabdian Masyarakat, 2024)
The rapid advancement of technology in the 5.0 era demands digital literacy as a crucial skill for teachers, particularly in designing technology-based learning. This community service program aims to introduce and train teachers at SMP Negeri 2 Kota Ambon in using Canva, a graphic design platform, as a tool to create creative and interactive learning media. Utilizing methods such as lectures, practice, and discussions, the program encompasses stages from needs analysis to evaluation of training outcomes. The results indicate an improvement in teachers' understanding, with an average rating classified as "excellent," while also helping students become more digitally literate and prepared for a technology-driven workforce. This program is expected to serve as a reference for other educational institutions in enhancing teachers' digital literacy through Canva.